Differential attention to attributes in utility-theoretic choice models - Trudy Ann Cameron; J. R. DeShazo (Journal of Choice Modelling, 2010)
We show in a theoretical model that the benefit from additional attention to the marginal attribute within a choice set depends upon the expected utility loss from making a suboptimal choice if it is ignored. Guided by this analysis, we then develop an empirical method to measure an individual's propensity to attend to attributes. As a proof of concept, we offer an empirical example of our method using a conjoint analysis of demand for programs to reduce health risks. Our results suggest that respondents differentially allocate attention across attributes as a function of the mix of attribute levels in a choice set. This behaviour can cause researchers who fail to model attention allocation to estimate incorrectly the marginal utilities derived from selected attributes. This illustrative example is a first attempt to implement an attention-corrected choice model with a sample of field data from a conjoint choice experiment.
Keywords: 330; attention to attributes; allocation of attention; conjoint choice; choice set design; bounded rationality; choice heuristics